IMPLEMENTASI MODEL PEMBELAJARAN COOPERATIVE TIPE NUMBER HEAD TOGETHER DALAM MENINGKATKAN PRESTASI BELAJAR PAK SISWAKELAS VIII SMP NEGERI 2 SALUPUTTI - Juniati Tangibali; Natasia Irene; Alfriyanti (CV. ADIBA AISHA AMIRA, 2023)
This research is about the Implementation of the Number Head Together Type of Cooperative Learning Model in Improving Cristian Religious Education Learning Achievement of Class VIII Students of SMP Negeri 2 Saluputti